EFFECTIVENESS OF ORAL HYGIENE INTERVENTION WITH HONEY IN PREVENTING VENTILATOR-ASSOCIATED PNEUMONIA (VAP) IN PATIENTS WITH MULTIPLE FRACTURES - Yustilawati, Eva; Andi Budiyanto Adi Putra; ilhamsyah; Nadilah Diana Muslimin (Homes Journal = Hospital Management Studies Journal, 2024)
Background: Fracture is the discontinuity of bone, caused by trauma or force. According to the World Health Organization (WHO), fractures have been increasing from 2020 to 2022. In 2020, fractures occurred in 2.7% (13 million people), in 2021 it was 3.8% (20 million people), and in 2022, the incidence rose to 4.2% (21 million people). Most patients diagnosed with fractures are treated in the ICU with mechanical ventilator support through an endotracheal tube (ETT). Prolonged treatment can lead to Ventilator Associated Pneumonia (VAP), which is the most susceptible type of nosocomial infection in the Intensive Care Unit. Objective:This research aims to examine the effectiveness of oral hygiene using honey in patients with multiple fractures and self-care deficit issues in preventing Ventilator Associated Pneumonia (VAP) in the ICU of Wahidin Sudirohusodo Makassar Hospital. Method:The method used was a case study employing observation sheets and documentation. Result: After the intervention was given for 3 consecutive days, the patient experienced oral health improvement, assessed by the BOAS score and MPS score. For the BOAS score, there was a significant change from moderate dysfunction (BOAS score 15) to mild dysfunction (BOAS score 8). For the MPS score, there was a significant change from poor (MPS score 7) to good (MPS score 4). Conclusion: Based on the evaluation results, it was found that the implementation of oral hygiene using honey can help.